Introduction to Sharon Dunwoody Memorial Issue. Issue 1 (February 2023) - Priest, Susanna; Kahlor, Lee Ann; Griffin, Robert J.
This introduction to our February 2023 issue is intended to provide context for the issue content, which presents multiple examples of the ongoing influence of the work of the late Sharon Dunwoody. Contemporary research articles, commentary pieces, and the introduction itself reflect Sharon's deep influence on science communication and science communication researchers and their work.